Submillimeter wave spectrum of the 12CH235Cl2 methylene chloride in the excited (v4=1) vibrational state up to 1.1 THz; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 336 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Khudyakova Yu. V. Yuliya Vadimovna; Vaks V. L. (2025, 2025)
The high resolution submillimeter wave spectrum of the 12CH235Cl2 methylene chloride was analyzed in the wide spectral region from 0.075 up to 1.090 THz. The 5451 lines with the maximum values of quantum number Jmax=98 and Kamax=24, which correspond to 4037 unresolved singlet and central lines of triplets and 1414 peripheral lines of triplets (this spectroscopic structure is due to partially resolved/unresolved Cl quadrupole coupling hyperfine structure), were assigned in the experimental spectra to the transitions of the (v4=1) vibrational state. Weighted fit of the rotational and centrifugal distortion parameters of the Watson Hamiltonian in A−reduction and Ir− representation, as well as of the Cl quadrupole coupling constants was made with the SPFIT/SPCAT package of Pickett. The obtained set of twenty rotational and centrifugal distortion parameters and three quadrupole coupling parameters reproduces values of the 4037 experimental multiplet centra with the drms=14 kHz and of the 1414 experimental peripheral lines of triplets with the drms=34 kHz. Comparison with the rotational and centrifugal distortion parameters of the (v4=1) vibrational state known in the literature was made and shown that the parameters known in the literature reproduce the same set of experimental data with an accuracy in 150–300 times worse in comparison with the results of the present study. At the same time, the obtained values of the quadrupole coupling χ−parameters show an excellent correspondence with the values of corresponding parameters recently obtained by Z. Kisiel (J Mol Spectrosc 2024; 406:111954)